Eco-Friendly Product Purchase Behavior Model: Application of Theory of Planned Behavior in Generation Z Consumers - Octavia, Ade; Sriayudha, Yayuk; Musnaini, Musnaini (Dinasti Publisher, 2024)
The use of environmentally friendly (eco-friendly) products is the best solution for maintaining environmental sustainability. The consumption behavior of Generation Z can be a starting point that has an important role if these young buyers actively contribute to promoting sustainable economic development and purchasing eco-friendly products. This study aimed to analyze (1) the relationship between consumer attitudes, subjective norms, and perceived controls with the purchase intention of eco-friendly products in generation Z consumers, and (2) the relationship between the purchase intention of eco-friendly products and eco-friendly product purchase behavior in generation Z consumers. The approach used was explanatory research with a quantitative analysis research method. The study population was Generation Z consumers in Jambi with a sample of 200 respondents. Non-probability sampling technique was used to select research samples. The instrument used was a research questionnaire. The data were analyzed using the Structural Equation Model (SEM/PLS) with the smartPLS analysis tool. The results showed that consumer attitudes have a significant effect on the purchase intention of eco-friendly products in Generation Z consumers. Whereas, subjective norms have no effect on the purchase intention of eco-friendly products in Generation Z consumers. Furthermore, there is a positive effect between behavioral controls and the purchase intention of eco-friendly products in Generation Z consumers. The purchase intention of Generation Z consumers has an effect on eco-friendly product purchase behavior. The results of this study are expected to be implemented in order to maintain environmental sustainability and a green economy as well as to contribute and become reference literature for academics, universities, local governments, consumers, and business actors.